2023
DOI: 10.2147/jir.s395229
|View full text |Cite
|
Sign up to set email alerts
|

The Value of the Monocyte to High-Density Lipoprotein Cholesterol Ratio in Assessing the Severity of Knee Osteoarthritis: A Retrospective Single Center Cohort Study

Abstract: Background Inflammatory responses and metabolic abnormalities play essential roles in the pathophysiology of osteoarthritis (OA). Our study aimed to evaluate the association between monocyte-to-high density lipoprotein-cholesterol ratio (MHR) and OA and compared it with other systemic inflammatory markers. Methods This study recruited 323 OA cases and age- and sex-matched 283 control participants during the same period. Demographic, clinical, and imaging data and labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…However, there is some information on MHR in inflammatory or musculoskeletal diseases. In a previous study that included 323 patients with knee osteoarthritis and 283 age-and sexmatched controls, MHR was significantly higher in patients than in healthy controls [28]. Moreover, MHR significantly correlated with the radiological severity.…”
Section: Discussionmentioning
confidence: 77%
“…However, there is some information on MHR in inflammatory or musculoskeletal diseases. In a previous study that included 323 patients with knee osteoarthritis and 283 age-and sexmatched controls, MHR was significantly higher in patients than in healthy controls [28]. Moreover, MHR significantly correlated with the radiological severity.…”
Section: Discussionmentioning
confidence: 77%
“…41 In addition, MHR has been indicated to have greater diagnostic significance in conditions such as tuberculosis and osteoarthritis. 42,43 In the prediabetic stage, an increase in monocytes count and pro-inflammatory subtypes has been observed. 18 In a 5-year cohort study, it was found that the dysregulation of circulating immune cells and inflammatory factors was associated with dynamic disruptions in glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%